Effects of over-winter green cover on groundwater nitrate and dissolved organic carbon concentrations beneath tillage land - COXON, CATHERINE ELIZABETH (Elsevier, 2012)
Application of over-winter green cover (e.g. cover crops) as a measure for reducing nitrate losses from tillage land has been frequently investigated, especially in the unsaturated zone. Monitoring of groundwater is less common in these studies. Studies on groundwater responses to different land treatments can be challenging because they can be influenced by various conditions, such as recharge, seasonal variations, and aquifer properties, often occurring at different time scales than surface water processes. The aim of this study was to evaluate groundwater nitrate (NO3--N) and dissolved organic carbon (DOC) concentration responses to different over-winter green covers: mustard, natural regeneration and no cover. A field experiment was designed and run for three years on tillage land underlain by a vulnerable sand and gravel aquifer in the south-east of Ireland. Results showed that over-winter green cover growth on tillage land can be an effective measure to reduce groundwater NO3--N concentrations. A significant decrease in groundwater NO3--N concentrations was observed under the mustard cover compared to no cover. All treatments, including no cover, showed a decline in groundwater NO3--N concentrations over time. A significant increase in groundwater DOC was also observed under the mustard cover. Although the overall groundwater DOC concentrations were low, the increased DOC occurrence in groundwater should be accounted for in carbon balances and could potentially enhance groundwater denitrification in cases where aquifer conditions may favour it.
PUBLISHED
Keywords: groundwater; nitrate; dissolved organic carbon; tillage